2008
DOI: 10.1103/physrevb.77.155424
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative adsorption ofO2molecules on O-precovered Fe(110) and Fe(100): Density-functional calculations

Abstract: The dissociative adsorption of O 2 molecules on clean and oxygen-precovered Fe͑110͒ and Fe͑100͒ surfaces has been studied from first principles. For the relatively open Fe͑100͒ surface, we find that along the most favorable reaction channel, O 2 dissociation remains a nonactivated process up to almost full monolayer coverage. The differential heat of adsorption decreases only slowly with increasing oxygen precoverage. The potential energy profile for dissociation shows a dip, which is indicative of the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
5
16
0
Order By: Relevance
“…For a coverage between 0.22 and 0.44 ML, h amounts between 1.07 Å and 1.11 Å, respectively. 42 These results agree with findings from Erley and Ibach, 30 where an assumed bonding length of 1.8 Å, between the Fe and O atoms accords with the stretching frequency observed for free FeO molecules by vibrational electron-energy-loss spectroscopy ͑EELS͒. For fourfold hollow sites of the adsorbed oxygen atoms this bonding length corresponds to h = 1.1 Å.…”
Section: E Vertical Positions Of Adsorbed Oxygen Atomssupporting
confidence: 87%
See 1 more Smart Citation
“…For a coverage between 0.22 and 0.44 ML, h amounts between 1.07 Å and 1.11 Å, respectively. 42 These results agree with findings from Erley and Ibach, 30 where an assumed bonding length of 1.8 Å, between the Fe and O atoms accords with the stretching frequency observed for free FeO molecules by vibrational electron-energy-loss spectroscopy ͑EELS͒. For fourfold hollow sites of the adsorbed oxygen atoms this bonding length corresponds to h = 1.1 Å.…”
Section: E Vertical Positions Of Adsorbed Oxygen Atomssupporting
confidence: 87%
“…2, we display a sketch of structural models for the two superstructures, which have been investigated experimentally [23][24][25][26][27][28][29][30][31][32][33][34][35] and theoretically [36][37][38][39][40][41][42] before. For both superstructures, the adsorbate atoms occupy fourfold hollow sites of the Fe substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies have shown that oxygen adsorbs dissociatively on iron surfaces [4]. It was also found that atomic O adsorption on Fe surfaces is a non activated process up to 1 monolayer (ML) coverage [5], while dissociative adsorption is non activated only for lower coverages (b0.5 ML) [5,6].…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, some recent studies for oxygen coverages of 0.22-0.67 ML [6] or 0.25 ML [28] reported higher stability of superstructures with O in the threefold coordinated hollow sites. The discrepancies in preference of adsorption places on the Fe(110) surface are puzzling, because most of the experimental works suggest that, at lower coverage, oxygen atoms adsorb in long bridge sites whereas for higher coverages they move to hollow sites before the surface iron-oxide structure is formed.…”
Section: Introductionmentioning
confidence: 96%
“…The related γ ER values (not available in the literature) have been chosen for a best global agreement with the data measured in this work over the whole range of studied concentrations. Dissociative adsorption of O 2 at the walls, which has been experimentally studied by molecular beams and modelled on clean Fe surfaces [87,88], has been tested with model simulations and has very small influence on the present H 2 / O 2 plasmas. In previous works [37][38][39], adsorptions of neutral molecules were considered negligible as compared with those of atoms and radicals.…”
Section: Modelmentioning
confidence: 99%